ANALISIS EVALUASI KINERJA PELAYANAN PUBLIK DI BPJS KETENAGAKERJAAN KCP RANTAU PRAPAT - Deni Irawan; Rahmi Syahriza (Lembaga Pengembangan Kinerja Dosen, 2025)
The aim of this research is to evaluate the quality of BPJS Employment services at the Rantau Parapat Public Service Mall. Through a qualitative descriptive approach, the author explains how BPJS Employment services are provided at the public service mall at BPJS Employment Rantau Parapat as a form of implementing excellent service in administrative reform. The results show that the quality of BPJS Employment services in public service malls in Rantau Parapat